Immunophenotypical characterization of canine mesenchymal stem cells from perivisceral and subcutaneous adipose tissue by a species-specific panel of antibodies. (October 2017) - Ivanovska, Ana; Grolli, Stefano; Borghetti, Paolo; Ravanetti, Francesca; Conti, Virna; De Angelis, Elena; Macchi, Francesca; Ramoni, Roberto; Martelli, Paolo; Gazza, Ferdinando; Cacchioli, Antonio
Abstract: Immunophenotypical characterization of mesenchymal stem cells is fundamental for the design and execution of sound experimental and clinical studies. The scarce availability of species-specific antibodies for canine antigens has hampered the immunophenotypical characterization of canine mesenchymal stem cells (MSC). The aim of this study was to select a panel of species-specific direct antibodies readily useful for canine mesenchymal stem cells characterization. They were isolated from perivisceral and subcutaneous adipose tissue samples collected during regular surgeries from 8 dogs. Single color flow cytometric analysis of mesenchymal stem cells (P3) deriving from subcutaneous and perivisceral adipose tissue with a panel of 7 direct anti-canine antibodies revealed two largely homogenous cell populations with a similar pattern: CD29 +, CD44 +, CD73 +, CD90 +, CD34 −, CD45 − and MHC-II − with no statistically significant differences among them. Antibody reactivity was demonstrated on canine peripheral blood mononuclear cells. The similarities are reinforced by their in vitro cell morphology, trilineage differentiation ability and RT-PCR analysis (CD90 +, CD73 +, CD105 +, CD44 +, CD13 +, CD29 +, Oct-4 + gene and CD31 − and CD45 − expression). Our results report for the first time a comparison between the immunophenotypic profile of canine MSC deriving from perivisceral and subcutaneous adipose tissue. The substantial equivalence between the two populations has practical implication on clinical applications, giving the opportunity to choose the source depending on the patient needs. The results contribute to routine characterization of MSC populations grown in vitro, a mandatory process for the definition of solid and reproducible laboratory and therapeutic procedures. Highlights: The design of MSC based therapeutic protocols requires an accurate cell characterization. Selection of a panel of 7 species specific anti-canine antibodies for flow cytometric characterization of canine AT-MSC Canine AT-MSC from subcutaneous and perivisceral adipose tissue have a similar immunophenotypic profile. Comparison of the immunophenotypical profile of AT-MSC from veterinary species, laboratory animals and human origin AT-MSC derived from animal species have a lower CD73 expression compared to human AT-MSC.